Youth Futures and a Masculine Development Ethos in the Regional Story of Uttarakhand. (August 2017) - Koskimaki, Leah
Research on the Uttarakhand region, which became a new state in 2000, has focused largely on agrarian livelihoods, religious rituals, development demands, ecological politics and the role of women in regional social movements. This essay discusses another dimension of the regional imaginary—that of a masculine development ethos. Based on ethnographic research and print media sources, this essay focuses on stories, politics, mobilities and imaginations of young men in the years immediately after the achievement of statehood. Despite increased outmigration of youth in search of employment, many young men expressed the dream of maintaining livelihoods in the familiar towns and rural spaces of Uttarakhand, describing their home region as a source of power and agency. In rallies and in print media, young (mostly upper caste) men expressed their disillusionment with the government and the promises of statehood, arguing that their aspirations for development and employment were left unfulfilled. Gendered stories of the region, told in Hindi in rallies and print media, contained references to local places, people and historical events and were produced through local connections and know-how, fostering a regional youth politics. The article argues that Uttarakhand as a region is shaped by the politics of local actors as well as embodied forms of aspiration, affiliation and mobility.